2016
DOI: 10.1016/s2214-109x(16)30064-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of bacterial meningitis: a time-series analysis

Abstract: Summary Background Bacterial meningitis, which is caused mainly by Neisseria meningitidis, Haemophilus influenzae, and Streptococcus pneumoniae, inflicts a substantial burden of disease worldwide. Yet, the temporal dynamics of this disease are poorly characterised and many questions remain about the ecology of the disease. We aimed to comprehensively assess seasonal trends in bacterial meningitis on a global scale. Methods We developed the first bacterial meningitis global database by compiling monthly inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 27 publications
5
41
2
2
Order By: Relevance
“…The power spectrum offers a p -value for each observation in each frequency. For instance, Paireau et al [43], consider the time series to be seasonal using a criterium of three consecutive years of significant p -values in a given frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The power spectrum offers a p -value for each observation in each frequency. For instance, Paireau et al [43], consider the time series to be seasonal using a criterium of three consecutive years of significant p -values in a given frequency.…”
Section: Discussionmentioning
confidence: 99%
“…There were a number of limitations to this study. There has been shown to be seasonal variations in the incidence of meningitis peaking in the winter months (Paireau et al, 2016;Palmgren, 2009), and a similar winter peak in the carriage rate in new recruits (Tyski et al, 2001), in this study the samples were collected outside of the winter period and so carriage may be lower. Immediate plating of swabs has been shown to result in higher detection of carriage (Caugant et al, 2007;Christensen et al, 2010;Cunningham et al, 2001;Roberts et al, 2009), however in this study swabs were plated up to 6 h after sampling, which may have led to lower observed carriage rates.…”
Section: Discussionmentioning
confidence: 61%
“…Third, in countries below -20°N (South America, Oceania and South Africa), the incidence of disease caused by any of the pathogens peaked June to July (winter season). 19 So our study area falls in the first belt where winter cases are explained by N. meningitides activity. A causal role of environmental factors in meningitis is still unknown.…”
Section: Airborne Infectionmentioning
confidence: 87%